Principles of instrumental analysis - Skoog, Dougls A. (Harcourt Brace College, 1992)
This book is divided into six major sections. Section I presents electronic circuit fundamentals, operational amplifiers, digital electronics and computers, signals, noise, data enhancement techniques, and figures of merit. Section II provides various branches atomic spectroscopy, including optical absortion, optical emission, and optical fluorescence spectrometry, atomic mass spectrometry, and atomic X-ray spectrometry. Section III treats molecular spectroscopy. Section IV discusses electroanalytical chemistry techniques including potentiometry, coulometry, and voltammetry. Section V presnets various types of chromatography and electrophoresis. Section VI discusses miscellaneous instrumental approaches to the solution of analytical problems including thermal, radiochemical, and automated methods